Protecting Journalists in the Digital Age: A Cross-Jurisdictional Legal Comparison of Indonesia and the Netherlands - Ari Rahmayani, Chanidia; Wulandari, Cahya; Qoiri, Mutmainah Nur; Winarsih; Pasaribu, Nauli Pinorsinta; Uliana Sianipar, Jennifer Margareth (Universitas Negeri Semarang, 2025)
This study examines the legal frameworks of Indonesia and the Netherlands in addressing doxing as an emerging threat to press freedom and the protection of journalists’ personal data. Although Indonesia has established several legal instruments, including the Press Law No. 40/1999, the amended Electronic Information and Transactions Law No. 1/2024, and the Personal Data Protection Law No. 27/2022. The existing regulations remain implicit, fragmented, and insufficient in providing legal certainty. Interviews conducted with three journalists from diverse professional backgrounds reveal that legal protection remains predominantly passive, with inadequate law enforcement against actors who perpetrate digital intimidation and attacks on journalists. In contrast, the Netherlands has adopted a more comprehensive regulatory approach through its constitutional guarantee of freedom of expression, the direct implementation of the General Data Protection Regulation (GDPR), the establishment of an independent data protection authority (Autoriteit Persoonsgegevens), and the enactment of a specific anti-doxing law in 2024 that prescribes clear criminal sanctions. Additionally, the PersVeilig protocol demonstrates a more institutionalized mechanism for safeguarding journalists against threats in both physical and digital environments. Comparative analysis highlights the pressing need for Indonesia to strengthen legal protections for journalists through a more integrated model. This study recommends the development of explicit anti-doxing regulation, the establishment of an independent data protection authority, and the creation of cross-institutional collaboration protocols to ensure the safety of journalists and uphold press freedom in the digital democratic ecosystem.